2011
DOI: 10.1590/s1519-38292011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Condições socioeconômicas e padrões alimentares de crianças de 4 a 11 anos: estudo SCAALA - Salvador/ Bahia

Abstract: OBJETIVOS: identificar os padrões alimentares de crianças e sua associação com o nível socioeconômico das famílias. MÉTODOS: estudo transversal com 1260 crianças de 4 a 11 anos, residentes em Salvador-Bahia que incluiu aplicação de um Questionário de Frequência Alimentar semi-quantitativo. Os padrões alimentares foram identificados, empregando-se análise fatorial por componentes principais. O nível socioeconômico foi avaliado por meio de um indicador socioeconômico composto. Regressão logística multivariada fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 19 publications
4
15
0
12
Order By: Relevance
“…This pattern of food consumption is similar to that identified in children from Salvador, consisting of fried foods, sweets, snacks and soda/artificial juice 25 . The "Western" food pattern observed in adolescents from Mato Grosso, also characterized by processed foods, dairy products, processed meats, sweetened drinks, fast food, fried banana and sweets 24 , with the exception of fruits and beans, was also similar to patterns found in this study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This pattern of food consumption is similar to that identified in children from Salvador, consisting of fried foods, sweets, snacks and soda/artificial juice 25 . The "Western" food pattern observed in adolescents from Mato Grosso, also characterized by processed foods, dairy products, processed meats, sweetened drinks, fast food, fried banana and sweets 24 , with the exception of fruits and beans, was also similar to patterns found in this study.…”
Section: Discussionsupporting
confidence: 76%
“…As its name suggests, the healthy pattern was characterized by high consumption of healthy food markers (salads, vegetables, fruits, beans and milk) and low consumption of items that characterize an unhealthy dietary pattern (pro- A study with children from Salvador/BA identified a similar dietary pattern, with a predominance of fruits, vegetables and grain legumes 25 . This pattern was also identified in students in other countries such as Scotland 26 and England 27 , where it was also called "healthy".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As variáveis de consumo alimentar adotadas para este trabalho são provenientes da análise fatorial realizada em estudo anterior 21 , utilizandose o método de Análise de Componentes Principais, o qual gerou o padrão alimentar e grupos de alimentos que o compõe, com base em questionário de frequência alimentar (QFA) semiquantitativo, validado por Matos et al 22 , composto por 98 alimentos, referente ao consumo alimentar nos últimos 12 meses. Detalhes sobre a análise para definição do padrão alimentar e dos grupos de alimentos característicos dessa amostra estudada podem ser encontrados no trabalho de D'Innocenzo et al 21 .…”
Section: Metodologiaunclassified
“…Detalhes sobre a análise para definição do padrão alimentar e dos grupos de alimentos característicos dessa amostra estudada podem ser encontrados no trabalho de D'Innocenzo et al 21 . No entanto, dispõe-se a seguir de breve metodologia para a definição dessas variáveis de consumo alimentar.…”
Section: Metodologiaunclassified